The Relevance of Rahmah El-Yunusiyah's Ideas to Contemporary Women's Education in Indonesia - Fitriyanti Fitriyanti; Eprianto Eprianto; Muhamad Fauzi; Abu Mansyur (Journal of Educational Sciences, 2026)
This study examines the transformation of women’s education in Indonesia through the educational thought of Rahmah El-Yunusiyah, a pioneering reformer who established the Diniyah Putri in Padang Panjang. Her initiatives emerged from a socio-historical context in which women had limited access to formal education due to patriarchal norms and colonial structures. The purpose of this study is to analyze Rahmah’s holistic and integrative educational concept, which combines religious sciences, general knowledge, character formation, and practical life skills as a comprehensive system for empowering Muslim women. Using a qualitative approach with literature and historical methods, this research draws upon primary sources—such as archival records, biographical documents, and early curricula of Diniyah Putri—alongside secondary scholarly works. The findings reveal that Rahmah successfully shifted the paradigm of women’s education from a domestic-centered model to a progressive framework that positions women as active agents in social and religious life. Her pedagogical model emphasizes moral integrity, intellectual competence, and social responsibility, making Diniyah Putri a pioneering institution of Islamic women’s education in Southeast Asia. The study concludes that Rahmah’s ideas remain highly relevant for contemporary educational development, offering a strategic foundation for strengthening the role of Muslim women as empowered, independent, and contributive members of society.